The use of teacher corrective feedback to help students improve their ESL writing - Bokhari, Noorhariani (2013)
The purpose of this study was to find out whether teacher’s corrective grammatical feedback could help improve students’ English as a Second Language (ESL) writing, Besides, it also to find out how far the feedbacks given help in enhancing students’ ability to self-correct the tenses errors as well as to improve their skills in writing and to determine the students and teachers’ views on the impact of corrective feedback in English as a Second Language (ESL) writing lesson. Data were gathered using qualitative means; from the students’ essays and semi-structured interviews. A total of thirty students and two teachers participated in this study. Both data were analyzed separately but were triangulated to give a more comprehensive account of the study. The results of the analysis showed that (1) despite the challenges both teachers faced in providing and students had in responding to the corrective feedback, they were aware of the importance and purpose of giving corrective feedbacks to help the students to be better in their writing, (2) even though the students had learned the basic rules of grammar in their previous lessons; they still have the tendency to make mistakes in their writing, (3) ) the role of teachers in providing good corrective feedbacks could be a tool for the students to be more proficient in their writing, and (4) there were tremendous changes in terms of the quality of the students’ ESL writing product after they had received the corrective feedbacks from their teachers. The study concluded that using corrective feedback in helping students is seen as positive and effective approach to be practised by ESL teachers. Both teachers and students believed that corrective feedback should be used widely as it could enhance the students ability in ESL writing classroom as it could enhance the students’ ability in ESL.